2020
DOI: 10.1108/rjta-11-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Are customers satisfied? Study of the problems currently prevailing in the plus size women’s wear market in Sri Lanka

Abstract: Purpose Plus size clothing is becoming a fashion trend worldwide due to the body positivity movement sparked off by the growing obesity rates and fat shaming incidents reported around the world. Although the problems relating to plus size clothing in the global context have been addressed, thereby establishing certain norms in the market, none of this work has proved helpful in assessing the level of customer satisfaction in the Sri Lankan plus size market. In view of this lacuna, this paper aims to probe cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Although consumers have diverse body shapes, most apparel companies developed garments according to one body shape. Seram and Kumarasiri (2020) surveyed 88 plus size women, aged 20-35 in Sri Lanka, and more than half of the participants had fit issues with RJTA 26,4 ready-to-wear garments because of various body shapes and sizing systems. Through interviewing three designers of selected brands that produce plus size garments, they discovered that none of those apparel companies used more than one fit model or mannequin to test the fit.…”
Section: Fit Perceptions Of Customized Garmentsmentioning
confidence: 99%
“…Although consumers have diverse body shapes, most apparel companies developed garments according to one body shape. Seram and Kumarasiri (2020) surveyed 88 plus size women, aged 20-35 in Sri Lanka, and more than half of the participants had fit issues with RJTA 26,4 ready-to-wear garments because of various body shapes and sizing systems. Through interviewing three designers of selected brands that produce plus size garments, they discovered that none of those apparel companies used more than one fit model or mannequin to test the fit.…”
Section: Fit Perceptions Of Customized Garmentsmentioning
confidence: 99%
“…The results revealed that PTQM practices as a whole significantly influenced job involvement but not job satisfaction, affective commitment or turnover intention of the machine operator-level employees. These findings are unique to the TQM literature and provide insights into the management of the Sri Lankan apparel organisations faced with the challenges in sustaining product quality (Dharmasiri and Ranasinghe, 2015;Fonseka and Fonseka, 2004;Wickramasinghe and Gamage, 2011;Ruwanpura and Wrigley, 2011;Seram and Kumarasiri, 2020) and in retaining their machine operator-level employees (Karunanayake and Welgama, 2016;Rajapaksha and Kappagoda, 2017;Welmilla, 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 87%
“…Então é mais por uma questão de segurança minha mesmo, porque às vezes você vê a roupa na internet... na modelo virtual fica boa e em você não fica". Assim, prevalece a preferência pelas lojas presenciais, que permitem aos consumidores a experiência de sentir os tecidos, avaliar as tonalidades e testar o caimento das peças (Seram & Kumarasiri, 2020). No Quadro 3 é possível visualizar os principais locais frequentados para adquirir roupas antes e depois da cirurgia.…”
Section: Análise E Discussão Dos Resultadosunclassified